Study of lymphatic drainage in malignant melanomas of the trunk - Priario, Julio C; Lago, Graciela; Borges, Freddy; Levin, Roberto; Touya, Eduardo (Cirugía del Uruguay, 1984)
First results obtained wilh the use of gammagraphic scanning employing colloidal ssmrc in the identifica• tion of drainage ganglionar groups in trunk melano• mas Authors propase the use of this procedure to deter• mine which ganglionar groups to extirpate, thus avoiding a quadruple ganglionar emptying or a limited extirpation, but chosen at random.